PENELUSURAN FUNGI ENDOFIT PADA DAUN KOPASANDA (Chromolaena odorata L.) YANG BERPOTENSI SEBAGAI PENGHASIL ANTIBAKTERI TERHADAP BAKTERI PENYEBAB INFEKSI KULIT - Rusli, Rusli; Kosman, Rachmat; Melinda, Pina (Fakultas Farmasi UMI, 2020)
The investigation for endophytic fungi of siam weed leaves (Chromolaena odorata L.) was conducted to obtain endophytic fungi potentially produced bioactive compound which were useful as an antibacterial. The research animed to obtain endophytic fungi isolate and determined the antibacterial activity against bacteria causing skin infection. The research was experimentally conducted including isolation of endophytic fungi, earthing, macroscopic examination, screening assay for antibacterial activity against bacteria, fermentation process for 21 days, and TLC separation and antibacterial testing by TLC-Bioautography against Staphylococcus aureus and Bacillus subtilis. The isolation results obtained 7 isolate followed by fermentation process with IFDK 03 isolate. The fermentate isolate of endophytic fungi showed Rf values of 0,2 anda 0,47 against Staphylococcus aureus and Bacillus subtilis. In conclusion, Siam weed leaves had isolate endophytic fungi with the potency as an antibacterial.